2017
DOI: 10.1111/jfpp.13395
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of debittered and germinated fenugreek (Trigonella foenum graecumL.) seed flour on the chemical characteristics, biological activities, and sensory profile of fortified bread

Abstract: Germination of fenugreek seed showed better nutraceutical profile as evaluated by in vivo (oral glucose tolerance and acute antihypertriglyceridemic tests) on rats and in vitro DPPH and enzyme inhibition assays (α‐glucosidase, lipase, and lipoxygenase). Attempts were made to develop debittered and germinated fenugreek seed flour (DGFSF) by soaking in acesulfame (0.25%, 8 hr), curd (1:1 in water, 8 hr) and sucrose (5%, 8 hr) solution at 1:4 (wt/vol) ratio for debittering and then germinated, of which curd showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 45 publications
6
33
0
1
Order By: Relevance
“…Also, increased weight of DFF‐added loaf might be because of less retention of gas in the blended dough, hence providing a dense texture. The results were comparable with the values reported in previous studies for fenugreek flour‐added WF breads (Chaubey et al, ) and flaxseed flour‐added WF rusks (Kaur et al, ). A significant ( p ≤ .05) linear decrease in loaf volume of DFF‐added rusks was observed with increase in DFF level from 5% to 20% (Table ).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Also, increased weight of DFF‐added loaf might be because of less retention of gas in the blended dough, hence providing a dense texture. The results were comparable with the values reported in previous studies for fenugreek flour‐added WF breads (Chaubey et al, ) and flaxseed flour‐added WF rusks (Kaur et al, ). A significant ( p ≤ .05) linear decrease in loaf volume of DFF‐added rusks was observed with increase in DFF level from 5% to 20% (Table ).…”
Section: Resultssupporting
confidence: 91%
“…But with increase in level of DFF in WF, the values of b * and Δ E progressively decreased from 5.85 to 3.12 and from 37.85 to 25.15, respectively. One previous study also reported decrease in L * and b * values whereas increase in a * values with addition of debittered and germinated fenugreek flour in bread (Chaubey et al, ). Color is an important quality parameter that is directly related to type and amount of raw material and processing conditions applied and influence the acceptability of final product.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations